2021
DOI: 10.1002/cncy.22489
|View full text |Cite
|
Sign up to set email alerts
|

Combined molecular and histologic end points inform cancer risk estimates for thyroid nodules classified as atypia of undetermined significance

Abstract: BACKGROUND: Thyroid nodules classified as atypia of uncertain significance (AUS) on fine-needle aspiration cytology are heterogeneous. Prior studies reported a higher risk of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP)/cancer among AUS nodules that had cytologic (AUS-C) versus architectural (AUS-A) atypia; however, such studies were generally confined to resected cohorts, introducing bias into risk calculations. The authors hypothesized that combined histologic and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Indeed, Veracyte now offers an MT that it markets for thyroid aspirates in TBS category V. 56,65,66 Laboratories have also reported widely variable AUS rates, including some that are significantly higher than those suggested by TBS, as well as widely variable rates of thyroid aspirates falling into TBS category I (nondiagnostic), which has implications for the analytic sensitivity of currently available molecular tests. [67][68][69] The advantage of the approach presented in the current study is its plasticity. Even when working with a heterogenous data set like that used here, as long as genetic information is collected consistently across specimens, the current approach is tolerant of differences in practice settings and imaging characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Veracyte now offers an MT that it markets for thyroid aspirates in TBS category V. 56,65,66 Laboratories have also reported widely variable AUS rates, including some that are significantly higher than those suggested by TBS, as well as widely variable rates of thyroid aspirates falling into TBS category I (nondiagnostic), which has implications for the analytic sensitivity of currently available molecular tests. [67][68][69] The advantage of the approach presented in the current study is its plasticity. Even when working with a heterogenous data set like that used here, as long as genetic information is collected consistently across specimens, the current approach is tolerant of differences in practice settings and imaging characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Veracyte now offers an MT that it markets for thyroid aspirates in TBS category V 56,65,66 . Laboratories have also reported widely variable AUS rates, including some that are significantly higher than those suggested by TBS, as well as widely variable rates of thyroid aspirates falling into TBS category I (nondiagnostic), which has implications for the analytic sensitivity of currently available molecular tests 67‐69 …”
Section: Discussionmentioning
confidence: 99%
“…Although as discussed previously surgical outcome data represent the gold standard for thyroid nodule characterization, not all indeterminate nodules are resected. As such, reliance on the high negative predictive value these molecular test offer for benign nodules can help provide an acceptable surrogate end point for nodules that are not surgically resected, thereby providing better ROM estimates than relying solely on resected nodules 10 . Incorporating this concept to a quality assurance program, leveraging these surrogate end points can help provide more robust and timely data on those thyroid FNAs assigned an indeterminate diagnosis when ancillary molecular testing is performed.…”
Section: Discussionmentioning
confidence: 99%
“…As such, reliance on the high negative predictive value these molecular test offer for benign nodules can help provide an acceptable surrogate end point for nodules that are not surgically resected, thereby providing better ROM estimates than relying solely on resected nodules. 10 Incorporating this concept to a quality assurance program, leveraging these surrogate end points can help provide more robust and timely data on those thyroid FNAs assigned an indeterminate diagnosis when ancillary molecular testing is performed. In these 2 studies, the paradigm of combining base metrics such as AUS rate or the AUS:M ratio with surrogate outcome data in the form of abnormal/suspicious molecular testing results provides a multivariate framework for explaining cytopathologist practice patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a negative GEC result reduces the ROM from 24% to 5%, supporting a simple follow-up for those patients ( 57 ). Furthermore, different papers found that patients with GEC suspicious nodules had higher ROM in cases with both architectural and nuclear atypia (57%) than in cases with architectural or nuclear atypia alone (19% and 45%, respectively) ( 58 61 ). Furthermore, an AUS/FLUS lesion with a Hürthle cell pattern endows with a low rate of GEC benign results and a very low ROM ( 62 ).…”
Section: Molecular Characterization Of Thyroid Lesionsmentioning
confidence: 99%